2020
DOI: 10.1016/j.cmi.2020.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Gram staining when predicting staphylococcal hospital-acquired pneumonia and ventilator-associated pneumonia: a systematic review and meta-analysis

Abstract: Background: There is no clear guidance on empirical antibiotic coverage against Staphylococcus aureus for hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP). Objective: To evaluate whether the presence of clusters of Gram-positive cocci in Gram staining of respiratory samples predicts S. aureus as HAP/VAP pathogen. Methods: Data sources were MEDLINE, PubMed, Embase, Scielo, CINAHL and Scopus, from inception to 15/07/2017 (update on 31/10/2019), and original data from a single-centre da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Yet, the diagnostic accuracy was higher when restricted to diagnosing VAP caused by S. aureus . In a recent meta-analysis 109 pooled data from 1,665 respiratory samples showed overall sensitivity and specificity of 68 and 95%; however, in clinical scenarios wherein the prevalence of S. aureus was between 5 and 20%, the negative predictive value was 95%.…”
Section: Diagnosismentioning
confidence: 95%
“…Yet, the diagnostic accuracy was higher when restricted to diagnosing VAP caused by S. aureus . In a recent meta-analysis 109 pooled data from 1,665 respiratory samples showed overall sensitivity and specificity of 68 and 95%; however, in clinical scenarios wherein the prevalence of S. aureus was between 5 and 20%, the negative predictive value was 95%.…”
Section: Diagnosismentioning
confidence: 95%
“…BAL (performed with or without concomitant bronchoscopy) is the sample that provides most information, as, in addition to cultures, cellularity analysis and PCR can be performed on the fluid. A recent meta-analysis showed that Gram staining of BAL performs well in detecting S. aureus 193 . Respiratory samples from patients with HAP or VAP have to be collected before the initiation of a new antibiotic treatment to avoid false-negative cultures.…”
Section: Microbiology and Laboratory Testsmentioning
confidence: 99%
“…Changes to antibiotic treatment, doses, or routes could offer different options when nonresponsive VAP is diagnosed. Antibiotics could then be selected based on risk factors for multidrug-resistant microorganisms, 39 surveillance cultures, Gram stain results, 40 conventional cultures, and molecular testing. Extended or continuous antibiotic infusions and measuring blood antibiotic concentrations may help optimize antibiotic dosing and reduce adverse events.…”
Section: Clinical Management Of Nonresponsive Vapmentioning
confidence: 99%